Proficiency Study of an Integrated Plug-In Hybrid Electric Vehicle with Cost Optimization - et. al., Dr.C.Santhana Lakshmi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present research paper acquaints with a cohesive method for a performance analysis of the hybrid electric vehicles. The inspiration of this research is given by the fact that the evolution happens in automotive sector, in recent times Hybrid Electric Vehicles are trending. As EV become hopeful alternatives for sustainable and cleaner energy emissions in transportation, the modelling and simulation of Hybrid Electric Vehicles has involved the researchers. This research is based on Mat lab modelling, both Modelling and simulation have become inseparable actions in any applied branch in engineering research and development. Nowadays, the nature of inseparability is even more obvious in the case of automotive industry. A set of 3 different research studies are projected and efficiency of designed Hybrid Electric Vehicle is tested through a series of simulation results. The power train machineries consist of a motor, a battery, a generator and a controller; modelled according to their mathematical concepts. Simulated electrical and mechanical results are plotted and discussed. The torque and speed circumstances during motoring and regeneration were used to determine the flow of energy, and performance of the drive. The credit is given by the accuracy of the model and simulation with the presented performance analysis methods. The improvement of this method is that the system performance can be validated to a large extent from an initial stage. The results can contribute to the real-world of developing H